Impact of non-gated computed tomography on the timing of invasive strategy of patients with non-ST-elevation acute coronary syndrome - Miyagawa, Masatsugu; Arai, Riku; Takahashi, Kurara; Nakajima, Yuki; Migita, Shohei; Mizobuchi, Saki; Tanaka, Yudai; Fukumoto, Katsunori; Morikawa, Tomoyuki; Mineki, Takashi; Kojima, Keisuke; Murata, Nobuhiro; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background This study aimed to examine the clinical role of non-gated computed tomography (CT) in ruling out fatal chest pain in patients with non-ST-elevation acute coronary syndrome (NSTE-ACS), with a focus on the time of arrival at the hospital to coronary angiography (CAG) and peak creatine kinase (CK) levels. Methods We retrospectively examined 196 NSTE-ACS patients who were admitted with urgently diagnosed NSTE-ACS and underwent percutaneous coronary intervention between March 2019 and October 2022. The patients were divided into three groups, namely, non-CT group, CT and defect− group, and CT and defect+ group, based on whether they underwent a CT scan and the presence or absence of perfusion defects on the CT image. Results After the initial admission for NSTE-ACS, 40 patients (20.4%) underwent non-gated CT prior to CAG. Among these 40 patients, 27 had a perfusion defect on the CT scan. The incidence of contrast-induced nephropathy was not different among the three groups. The CT and defect+ group had a shorter arrival-to-CAG time than that of the non-CT group. In NSTE-ACS patients with elevated CK levels, the CT and defect+ group had lower peak CK levels than those in the non-CT group. Conclusion NSTE-ACS patients with perfusion defects on non-gated CT had a shorter time from arrival to CAG, which might be associated with a lower peak CK. Non-gated CT might be useful for early diagnosis and early revascularization in the clinical setting of NSTE-ACS.